PENGARUH DIMENSI-DIMENSI KEPEMIMPINAN TRANSFORMASIONAL DAN TRANSAKSIONAL PADA KINERJA KARYAWAN - Prajogo, Wisnu (Modus Journals, 2013)
This article is aimed to test the infunce of charisma, intellectual stimulation, inspirational motivation and individualized consideration as dimensions of transformational leadership to employee performance measured by in-role and extra role per formance. This artcle is also examine the infuence of contingent reward and management by exception as dimensions of transactional leadership to employee performance measured with in-role and extra role performance. Five hundred and four manufacturing sector employees participated in this reseach. This research found that almost all of tranformational and transactional leadership dimensions has positive infuence to employee performance measured with in- role and extra role performance.Keywords : transformational leadership, transactional leadership, in-role performance, extra-role performance